2020
DOI: 10.1093/cvr/cvaa298
|View full text |Cite
|
Sign up to set email alerts
|

Dietary carbohydrates restriction inhibits the development of cardiac hypertrophy and heart failure

Abstract: Aims A diet with modified components, such as a ketogenic low-carbohydrate (LC) diet, potentially extends longevity and healthspan. However, how a LC diet impacts on cardiac pathology during hemodynamic stress remains elusive. This study evaluated the effects of a LC diet high in either fat (Fat-LC) or protein (Pro-LC) in a mouse model of chronic hypertensive cardiac remodeling. Methods and Results Wild-type mice were subject… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
34
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(34 citation statements)
references
References 39 publications
0
34
0
Order By: Relevance
“…It is well-known that mammalian target of rapamycin (mTOR) signaling is involved in the pathogenesis of cardiac hypertrophy and diabetic nephropathy. Ketone bodies have a protective effect on cardiac hypertrophy and diabetic nephropathy by inhibiting mTOR signaling [118,119]. In addition, ketone body inhibits class I histone deacetylases (HDACs) and activate Notch signaling in intestinal epithelial cells, thereby promoting stem cell self-renewal [120].…”
Section: Ketone Body Supplementation and Sglt2 Inhibitorsmentioning
confidence: 99%
“…It is well-known that mammalian target of rapamycin (mTOR) signaling is involved in the pathogenesis of cardiac hypertrophy and diabetic nephropathy. Ketone bodies have a protective effect on cardiac hypertrophy and diabetic nephropathy by inhibiting mTOR signaling [118,119]. In addition, ketone body inhibits class I histone deacetylases (HDACs) and activate Notch signaling in intestinal epithelial cells, thereby promoting stem cell self-renewal [120].…”
Section: Ketone Body Supplementation and Sglt2 Inhibitorsmentioning
confidence: 99%
“…This is significantly higher in diabetic patients at baseline or in response to fasting in non-diabetic patients. We have previously shown that 1 mM βHB affects signaling in cardiomyocytes [10]. Therefore, we chose dosages of βHB ranging from 0.1 to 10 mM.…”
Section: βHb Upregulates Trx1mentioning
confidence: 99%
“…Since mTOR is regulated by multiple mechanisms, βHB may affect the overall activity of mTOR through multiple mechanisms, both positively and negatively. For example, βHB inhibits mTOR activation and cardiomyocyte hypertrophy induced by phenylephrine, an agonist of the α1-adrenergic receptor [10]. Phenylephrine-induced mTOR activation is mediated by Erk, and phenylephrine-induced Erk activation is sensitive to antioxidant treatment [21,22].…”
Section: Ketone Bodies In Mtor Regulationmentioning
confidence: 99%
See 1 more Smart Citation
“…However, emerging evidence suggests the possibility that ketone metabolic modulation might become a viable treatment paradigm for HF [137,139]. Recent studies indicate that enhanced myocardial ketone use is adaptive in HF, and limited data demonstrate beneficial effects of exogenous ketone therapy in studies of animal models [140] and humans with HF [138,[140][141][142][143][144][145][146]. As noted in a recent review from Selvaraj and colleagues, "Although a number of important questions remain regarding the use of therapeutic ketosis and mechanism of action in HF, current evidence suggests potential benefit, in particular, in HF with reduced ejection fraction, with theoretical rationale for its use in HF with preserved ejection fraction.…”
Section: Heart Failure (Hf)mentioning
confidence: 99%